Age‐related changes in microRNAs expression in cruciate ligaments of wild‐stock house mice - Yalda A. Kharaz; Katarzyna Goljanek‐Whysall; Gareth Nye; Jane L. Hurst; Anne McArdle; Eithne J. Comerford (Physiological Reports, 2022)
Abstract Cruciate ligaments (CL) of the knee joint are injured following trauma or aging. MicroRNAs (miRs) are potential therapeutic targets in musculoskeletal disorders, but there is little known about the role of miRs and their expression ligaments during aging. This study aimed to (1) identify if mice with normal physical activity, wild‐stock house mice are an appropriate model to study age‐related changes in the knee joint and (2) investigate the expression of miRs in aging murine cruciate ligaments. Knee joints were collected from 6 and 24 months old C57BL/6 and wild‐stock house mice (Mus musculus domesticus) for ligament and cartilage (OARSI) histological analysis. Expression of miR targets in CLs was determined in 6‐, 12‐, 24‐, and 30‐month‐old wild‐stock house mice, followed by the analysis of predicted mRNA target genes and Ingenuity Pathway Analysis. Higher CL and knee OARSI histological scores were found in 24‐month‐old wild‐stock house mice compared with 6‐ and 24‐month‐old C57BL/6 and 6‐month‐old wild‐stock house mice (p < 0.05). miR‐29a and miR‐34a were upregulated in 30‐month‐old wild‐stock house mice in comparison with 6‐, 12‐, and 24‐month‐old wild‐stock house mice (p < 0.05). Ingenuity Pathway Analysis on miR‐29a and 34a targets was associated with inflammation through interleukins, TGFβ and Notch genes, and p53 signaling. Collagen type I alpha 1 chain (COL1A1) correlated negatively with both miR‐29a (r = −0.35) and miR‐34a (r = −0.33). The findings of this study support wild‐stock house mice as an appropriate aging model for the murine knee joint. This study also indicated that miR‐29a and miR‐34a may be potential regulators of COL1A1 gene expression in murine CLs.